2017
DOI: 10.1007/s00268-017-4266-2
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐inflammatory Effects of Enhanced Recovery Programs on Early‐Stage Colorectal Cancer Surgery

Abstract: The effects of ERP on GI recovery are correlated with the compliance of ERP and could be mediated at least in part by mPGES1, HPGDS and COX-2. Furthermore, mPGES1 shows promise as a therapeutic target to further reduce POI duration among ERP patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 51 publications
0
11
0
1
Order By: Relevance
“…A key consideration for this research is whether these results are clinically relevant within a modern ERAS framework of perioperative care. Current evidence suggests that, despite the use of ERAS, POI still occurs in as many as 25–30% of patients after elective colorectal surgery . Venara et al .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A key consideration for this research is whether these results are clinically relevant within a modern ERAS framework of perioperative care. Current evidence suggests that, despite the use of ERAS, POI still occurs in as many as 25–30% of patients after elective colorectal surgery . Venara et al .…”
Section: Discussionmentioning
confidence: 99%
“… recently looked at the expression of COX‐2 mRNA in pathology specimens from patients who underwent elective colorectal surgery and found that ERAS patients had significant reductions in COX‐2 mRNA expression compared with patients who did not follow an ERAS pathway. Of particular interest was that laparoscopic surgery, compared with laparotomy, did not significantly reduce levels of COX‐2 mRNA . This suggests that there may be additional benefits of short term COX‐2 selective NSAID use in additional to core ERAS principles.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Enhanced recovery protocols may improve ileus through fast-track care pathways which aim to maintain normal organ function and reduce the postoperative stress response. 6 Non-steroidal anti-inflammatory drugs (NSAIDs) are recommended by enhanced recovery protocols after elective colorectal surgery. 7 They are desirable for avoiding undesirable effects of opioid analgesia, such as constipation, sedation and respiratory depression.…”
Section: Introductionmentioning
confidence: 99%